ANALISIS DAMPAK PERUBAHAN SOSIAL PASKA PEMBANGUNAN JEMBATAN TAYAN DI DUSUN PIASAK KECAMATAN TAYAN HILIR - Tribuana, Syahbani Nur; Bahari, Yohanes; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this undergraduate thesis is â€œThe Impact Social Change Analysis After Tayanâ€™s Bridge Construction at Dusun Piasak Kecamatan Tayan Hilirâ€. The general problem of this study is â€œHow the impact social change analysis after Tayanâ€™s bridge contruction at Dusun Piasak Kecamatan Tayan Hilirâ€. Sub problems are (1) How the positive impact social change analysis after Tayanâ€™s bridge contruction at Dusun Piasak Kecamatan Tayan Hilir, (2) how negative impact social change analysis after Tayanâ€™s bridge contruction at Dusun Piasak Kecamatan Tayan Hilir. The purpose of this study to analyze social change impact after Tayanâ€™s bridge contruction at Dusun Piasak Kecamatan Tayan Hilir. The research was conducted by using qualitative approach with descriptive research method. The techniques of data collection were observation techniques, interviews and documentation studies while data collection tools were observation guidelines, interview guidelines, field notes and documents. The result of this study showd : (1) The positive impacts of social change that felt by dusun Piasak people are easier and faster when doing their daily activities and social integration between villages is increasing. (2) The negative impacts of social change that felt by dusun Piasak people are poverty and unemployement are increasing.Â Key Words : Social change impact, Dusun Piasak, Tayan bridge